Customer-oriented strategic information systems - Jackson, Ivan (School of Management Working Papers, 1992)
A major problem facing Information Systems (IS) managers is how to plan for a new corporate environment that is emerging as the result of increased competition, both national and international. The changes that have been brought about have been dramatic and far-reaching. Nowhere does this impact more than in application of information technology (IT) to corporate activities. In particular, the IS manager needs to be able to plan for systems that support the current emphasis on providing improved products and improved customer services. The accent is now on the development of "strategic" information systems (SIS), positioned so as to gain a "competitive advantage" (CA). However, the current planning models do not adequately explain how one goes about developing a plan for a "customer-oriented" strategic system. This paper attempts to redress that omission. A start is made with a manufacturing model which is modified slightly to be customer-focused and in a form more familiar to IS people. The potential IT opportunities inherent in the various manufacturing processes are then highlighted as the manufacturing sector struggles to maintain its competitive position. A transition is then made from the manufacturing environment to an "information factory" environment. The result is a model that can be usefully used for developing an IT plan and especially as an aid in the planning of customeroriented strategic systems.